Effect of implicit teaching strategy on basketball players - Camacho Lazarraga, Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Incidental processes provide advantages to the basketball player, since they free resources for other cognitive processes. The objective is to analyze if implicit learning reduces stress and produces an effect on motor actions. Twenty-four students participated. Four experimental conditions were designed with temporal, motor and combination of both limitations. The modification in the practice conditions significantly influences the perceived effort of the players and certain individual and collective variables of the game. It is concluded that we can consider the temporal constraint as an effective means to increase the mental load in the training process.